Alternative horticultural practices to replace a cold storage period to break dormancy in red raspberries (Rubus idaeus L.) - Brink, Judith Elizabeth (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1998.